Carbon Dioxide Capture Performance of Mesostructured Adsorbent Impregnated with Polyethylenimine - Chien-Hung Chen; Ching-Tsung Yu; Yu-Fei Chang (International Journal of Engineering and Technology Innovation, 2024)
This study aims to investigate the CO2 uptake performance of mesostructured adsorbents, such as Mobil Composition of Matter No. 41 (MCM-41), Santa Barbara Amorphous-15 (SBA-15), and multi-walled carbon nanotubes (MWNTs), modified with polyethylenimine (PEI). Mesoporous materials are loaded with 50 wt.% PEI using a wet impregnation method. CO2 kinetic experiments of the PEI-modified adsorbents are conducted by a thermogravimetric method. The results reveal that the CO2 adsorption capacities of the PEI/MCM-41, PEI/SBA-15, and PEI/MWNTs composites are 2.02, 3.06, and 2.93 mmol/g, respectively, under 15% CO2 flow at 348 K. The lower CO2 adsorption capacity of PEI/MCM-41 (2.02 mmol/g) is attributed to its poor porosity. The PEI/MWNTs composite has the fastest CO2 adsorption and desorption kinetics at the same temperature, compared to other PEI-modified adsorbents. These results suggest that MWNTs might play a significant “separator” role in effectively dispersing the PEI molecular chains on the mesostructured adsorbent.